1994
DOI: 10.2118/24974-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Shale Stabilization: Water Transport Through Shales

Abstract: One area where water-based muds need improved performance is in shale inhibition. However, before existing mud syste'11s can be improved, the mechanisms by which water invades shales and how present-day inhibitive additives operate must be fully understood. An experimental technique has been developed that uses radioactive tracers to monitor the progress of water and selected dissolved ions through a shale core plug. By varying experimental parameters, such as water composition and applied pressure drop, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…• The measured changes in rock strength were consistent with industry-accepted IEF osmotic pressure theory [10][11][12] and IEF membrane efficiency theory 13 for shale-fluid interaction. • An IEF with a WPS equal to the West Africa shale connate water salinity (e.g., a 'balanced' activity fluid having a WPS of 150,000 ppm calcium chloride) would have weakened the shale more than the intermediate WPS IEF.…”
Section: Previous Experimental Worksupporting
confidence: 77%
“…• The measured changes in rock strength were consistent with industry-accepted IEF osmotic pressure theory [10][11][12] and IEF membrane efficiency theory 13 for shale-fluid interaction. • An IEF with a WPS equal to the West Africa shale connate water salinity (e.g., a 'balanced' activity fluid having a WPS of 150,000 ppm calcium chloride) would have weakened the shale more than the intermediate WPS IEF.…”
Section: Previous Experimental Worksupporting
confidence: 77%
“…As for the investigations into the relationship between imbibition and ion diffusion, Ballard et al (1994) and Zolfaghari et al (2014) proposed that the ion diffusion rate is similar to the imbibition rate, depending on permeability, porosity, clay content and contact surface area. Ghanbari et al (2013) conducted imbibition/diffusion experiments and found that the behaviors of imbibition curves are well correlated to that of diffusion curves.…”
Section: Introductionmentioning
confidence: 99%
“…This result can be partially explained by osmosis effect. The electrically charged clay layers existing in the shale samples can act as semi-permeable membrane that restrict the passage of solute without affecting the passage of solvent (Steiger 1982;Mitchel 1993;Ballard et al 1994). Once low salinity water contacts with the clay particle existing in the shale samples, water molecules flow from low salinity side (imbibition fluid) of semi-permeable membrane to the high salinity side (pore water).…”
Section: Comparison Of Water Imbibition In Confined and Unconfined Samentioning
confidence: 99%